A3_1 Distortion: The Maths Behind The Magic - Manley, Max; Flood, Laura; Holland, Katie; Leversha, Thomas (Physics Special Topics, 2022)
In this paper, we are investigating and creating mathematical models for two different distortion types. We have succeeded in creating these models, as proven from our plots, and have explored the idea of applying these models to a simple speaker circuit.